Kualitas Pelayanan, Harga, dan Keputusan Pembelian Go-Food di Kota Palembang - Azizah, Siti Noor; Maulana, Ahmad (Jurnal Ilmu Manajemen, 2024)
This study aims to find out the effect of service quality and price on GoFood purchase decisions on general users of GoJek app services in Palembang City. GoFood applications are currently in high demand by many consumers or the public. This is because lifestyle changes are all practical, flexible, and more efficient. This study discusses the Palembang city community in the use of GoFood application services that are seen as quality of service (X1) and price (X2) against purchase decisions (Y), with the spread of questionnaires of as many as 100 respondents. The results will be collected is then analyzed using multiple regression analysis techniques that have been tested for validity and reliability. The results of this study show that, there is a positive and partial significance between the quality of service variable by purchase decision, and the price variable by purchase decision, There is a positive and significant simultaneous effect of service quality and price on GoFood purchase decisions in Palembang. This means that the people of Palembang will increase the purchase of food and drinks through GoFood application services.